Effect of Co-culturing Fibroblasts in Human Skeletal Muscle Cell Sheet on Angiogenic Cytokine Balance and Angiogenesis - Thummarati, Parichut; Kino-oka, Masahiro (Frontiers in Bioengineering and Biotechnology, 2020)
Skeletal muscle comprises a heterogeneous population of myoblasts and fibroblasts. Autologous skeletal muscle myoblasts are transplanted to patients with ischemia to promote cardiac regeneration. In damaged hearts, various cytokines secreted from the skeletal muscle myoblasts promote angiogenesis and consequently the recovery of cardiac functions. However, the effect of skeletal muscle fibroblasts co-cultured with skeletal muscle myoblasts on angiogenic cytokine production and angiogenesis has not been fully understood. To investigate these effects, production of vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF) was measured using the culture medium of monolayers prepared from various cell densities (mono-culture) and proportions (co-culture) of human skeletal muscle myoblasts (HSMMs) and human skeletal muscle fibroblasts (HSMFs). HSMM and HSMF mono-cultures produced VEGF, whereas HSMF mono-culture produced HGF. The VEGF productivity observed in a monolayer comprising low proportion of HSMFs was two-fold greater than that of HSMM and HSMF mono-cultures. The production of VEGF in HSMMs but not in HSMFs was directly proportional to the cell density. VEGF productivity in non-confluent cells with low cell-to-cell contact was higher than that in confluent cells with high cell-to-cell contact. The dynamic migration of cells in a monolayer was examined to analyze the effect of HSMFs on myoblast-to-myoblast contact. The random and rapid migration of HSMFs affected the directional migration of surrounding HSMMs, which disrupted the myoblast alignment. The effect of heterogeneous populations of skeletal muscle cells on angiogenesis was evaluated using human umbilical vein endothelial cells (HUVECs) incubated with fabricated multilayer HSMM sheets comprising various proportions of HSMFs. Co-culturing HSMFs in HSMM sheet at suitable ratio (30 or 40%) enhances endothelial network formation. These findings indicate the role of HSMFs in maintaining cytokine balance and consequently promoting angiogenesis in the skeletal muscle cell sheets. This approach can be used to improve transplantation efficiency of engineered tissues.